Transdisciplinary approach for the development of exploratory research with adults and children - Larrosa, Manuel; Wives, Leandro; Rodés, Virginia; Corbacho, Ana; Minini, Lucía; Ortegón, Oscar; Salenave, Brenda (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2024.242380, 2024)
This article describes an experience of a transdisciplinary approach for the exploratory study of a student reward system. Differentiated techniques were used to collect data, whether they were aimed at adults or students. To delve into the object of study, a mixed, quantitative and qualitative approach was carried out. Through the triangulation of the various data obtained and through both, statistical and supported by Text Mining and Natural Language Processing analysis techniques, was made visible the behavior of the students when using the tool focus of analysis.